2023
DOI: 10.1371/journal.pone.0281246
|View full text |Cite
|
Sign up to set email alerts
|

Determining the influence of LPI, GCI and IR on FDI: A study on the Asia and Pacific Region

Abstract: This study examines the impact of the Logistics Performance Index (LPI), Global Competitiveness Index (GCI) and Interest Rates (IR) on Foreign Direct Investment (FDI) for the Asia & Pacific region. The study is original as extensive evidence on the impact of LPI, GCI and IR on FDI in the Asia & Pacific region are examined initially. For the years 2007, 2010, 2012, 2014, 2016 and 2018, data was gathered for 33 nations in the Asia and Pacific area. Data analysis was performed using a panel regression mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…This study also outlines forms of potential moderators of the relationship between FDI and DE (Berrill et al , 2020). We postulated that the presence of more minor formal institutional distinctions, logistics and information and ICT could assist in relieving the potential likelihood provided by FDI to entrepreneurial activity locally (Chen and Jiang, 2023; Wannisinghe et al , 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This study also outlines forms of potential moderators of the relationship between FDI and DE (Berrill et al , 2020). We postulated that the presence of more minor formal institutional distinctions, logistics and information and ICT could assist in relieving the potential likelihood provided by FDI to entrepreneurial activity locally (Chen and Jiang, 2023; Wannisinghe et al , 2023).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that liberalisation under RCEP affects FDI through both FDI liberalisation and trade liberalisation, and these two paths encourage a significant increase in FDI to China [15].Pasindu et al consider the Logistics Performance Index, the Global Competitiveness Index and the interest rate to be the three main factors affecting FDI, of which the LPI has a significant impact on the FDI of India , Korea, Lebanon and Oman positively affected FDI, while China, Kuwait and the Philippines were negatively affected [16]. Other studies have shown that the host country's GDP, openness to the outside world, labour costs, and technological level can affect the country's ability to absorb OFDI.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Global FDI has become a significant phenomenon in recent years due to globalisation, the rapid expansion of international trade, economic interdependence, and inter-regional trade agreements [ 10 ]. Moreover, international trade is essential because no economy in the world is entirely self-sufficient.…”
Section: Introductionmentioning
confidence: 99%